Assessment of silicone rubber/lead oxide composites enriched with Bi2O3, WO3, BaO, and SnO2 nanoparticles for radiation shielding applications - Alresheedi, Mohammed Thamer; Elsafi, Mohamed; Aladadi, Yosef T.; Abas, Ahmad Fauzi; Ganam, Abdullrahman; Sayyed, M. I.; Mahdi, Mohd Adzir (Multidisciplinary Digital Publishing Institute, 2023)
This study aimed to prepare silicone rubber composites with heavy metal oxide nanoparticles for gamma ray shielding applications. Different heavy metal oxide nanoparticles were incorporated into the silicone rubber matrix, and the prepared composites were characterized for their thermal, mechanical, and radiation shielding properties. The density of the prepared SR samples ranged from 1.25 to 2.611 g·cm−3, with SR-2 having the highest density due to the presence of lead oxide. Additionally, the thermal stability of the materials improved with the addition of HMO nanoparticles, as indicated by TGA results. The prepared SR materials showed ultimate deformation displacement ranging from 14.17 to 21.23 mm, with the highest value recorded for SR-3 and the lowest for SR-2. We investigated the transmission factor (TF) of gamma rays through silicone rubber (SR) composites with different heavy metal oxide (HMO) nanoparticles. The addition of HMOs resulted in a decrease in TF values, indicating improved radiation shielding performance. The TF was found to be lowest in SR-5, which contained 15% of Bi2O3, WO3, BaO, and Zr2O3 each. The linear attenuation coefficient (LAC) of the SR samples was also evaluated, and it was found that the incorporation of HMOs increased the probability of photon interactions, leading to improved radiation protection effectiveness. The half-value layer (HVL) of the SR samples was also examined, and it was found that the addition of HMOs resulted in a significant reduction in HVL values, particularly at low energy levels. SR-5 had the lowest HVL among the group, while SR-2, SR-3, and SR-4 had higher HVL values. These results demonstrate the effectiveness of using HMOs in enhancing the radiation shielding properties of SR composites, particularly for low-energy gamma rays.